A Complex Remainder Problem

Algebra Level 3

If polynomial f ( x ) = x 2018 + A x + B 2018 f(x)=x^{2018}+Ax+B-2018 is divisible by x 2 + x + 1 x^2+x+1 for all reals x x . Find A + B A+B .

Hint: It's in the title of the problem!

You can try more of my fundamental problems here .


The answer is 2020.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Zico Quintina
Jul 2, 2018

Since x 2 + x + 1 x^2 + x + 1 is a factor of f ( x ) f(x) , its zeroes, ω \omega and ω 2 \omega^2 (see note below), must also be roots of f ( x ) f(x) . Then we have

f ( ω ) = 0 ω 2018 + A ω + B 2018 = 0 ( ω 3 ) 672 ω 2 + A ω + B 2018 = 0 ω 2 + A ω + B 2018 = 0 [ Since ω 3 = 1 ] ( ω 2 + ω + 1 ) + ( A 1 ) ω + B 2019 = 0 ( A 1 ) ω + B 2019 = 0 [ Since ω 2 + ω + 1 = 0 ] \begin{array}{rllll} f(\omega) = \ \ 0 \\ \\ \omega^{2018} + A\ \omega + B - 2018 = \ \ 0 \\ \\ (\omega^3)^{672} \cdot \omega^2 +A\ \omega + B - 2018 = \ \ 0 \\ \\ \omega^2 +A\ \omega + B - 2018 = \ \ 0 & & & \small \text{[ Since } \omega^3 = 1 \ ] \\ \\ (\omega^2 + \omega + 1) + (A - 1)\ \omega + B - 2019 \ \ = 0 \\ \\ (A - 1)\ \omega + B - 2019 \ \ = 0 & & & \small \text{[ Since } \omega^2 + \omega + 1 = 0 \ ] \end{array}

Now we just need to equate coefficients. Since ω \omega is complex, we must have A 1 = 0 A - 1 = 0 and B 2019 = 0 B - 2019 = 0 so our answer is A + B = 2020 A + B = \boxed{2020}

Note: The equation x 3 = 1 x^3 = 1 can be re-written as ( x 1 ) ( x 2 + x + 1 ) = 0 (x - 1)(x^2 + x + 1) = 0 ; the second factor yields the complex roots 1 ± 3 i 2 \frac{-1 \pm \sqrt{3}i}{2} . These complex cube roots of unity are usually called ω \omega and ω 2 \omega^2 as it's easily verified that each is the square of the other.

Great solution!

donglin loo - 2 years, 11 months ago
Donglin Loo
Jul 2, 2018

f ( x ) = x 2018 + A x + B 2018 f(x)=x^{2018}+Ax+B-2018

We can let f ( x ) = ( x 2 + x + 1 ) Q ( x ) f(x)=(x^2+x+1)Q(x)

x 2018 + A x + B 2018 = ( x 2 + x + 1 ) Q ( x ) x^{2018}+Ax+B-2018=(x^2+x+1)Q(x)

x 2018 2018 = ( x 2 + x + 1 ) Q ( x ) A x B \Rightarrow x^{2018}-2018=(x^2+x+1)Q(x)-Ax-B

We know that x 3 1 = ( x 1 ) ( x 2 + x + 1 ) x^3-1=(x-1)(x^2+x+1)

So we can rewrite x 2018 2018 x^{2018}-2018 as follows:

x 2018 2018 x^{2018}-2018

= ( x 2018 x 2015 ) + ( x 2015 x 2012 ) + ( x 2012 x 2009 ) + . . . + ( x 5 x 2 ) + x 2 2018 =(x^{2018}-x^{2015})+(x^{2015}-x^{2012})+(x^{2012}-x^{2009})+...+(x^{5}-x^{2})+x^2-2018

= x 2015 ( x 3 1 ) + x 2012 ( x 3 1 ) + x 2009 ( x 3 1 ) + . . . + x 2 ( x 3 1 ) + x 2 2018 =x^{2015}(x^3-1)+x^{2012}(x^3-1)+x^{2009}(x^3-1)+...+x^{2}(x^3-1)+x^2-2018

= ( x 3 1 ) ( x 2015 + x 2012 + x 2009 + . . . + x 2 ) + x 2 2018 =(x^3-1)(x^{2015}+x^{2012}+x^{2009}+...+x^{2})+x^2-2018

= ( x 2 + x + 1 ) ( x 1 ) ( x 2015 + x 2012 + x 2009 + . . . + x 2 ) + x 2 2018 =(x^2+x+1)(x-1)(x^{2015}+x^{2012}+x^{2009}+...+x^{2})+x^2-2018

= ( x 2 + x + 1 ) ( x 1 ) ( x 2015 + x 2012 + x 2009 + . . . + x 2 ) + x 2 + x + 1 x 2019 =(x^2+x+1)(x-1)(x^{2015}+x^{2012}+x^{2009}+...+x^{2})+x^2+x+1-x-2019

= ( x 2 + x + 1 ) [ ( x 1 ) ( x 2015 + x 2012 + x 2009 + . . . + x 2 ) + 1 ] x 2019 =(x^2+x+1)[(x-1)(x^{2015}+x^{2012}+x^{2009}+...+x^{2})+1]-x-2019

By comparing coeffiecients, A = 1 , B = 2019 A=1, B=2019

A + B = 2020 \therefore A+B=2020


Alternative approach: Complex numbers-Euler's formula

Let f ( x ) = ( x 2 + x + 1 ) Q ( x ) f(x)=(x^2+x+1)Q(x)

When x 2 + x + 1 = 0 x^2+x+1=0

x = 1 ± 3 i 2 = e ± 2 π 3 x=\cfrac{-1\pm\sqrt{3}i}{2}=e^{\pm\cfrac{2\pi}{3}}

By Remainder Factor Theorem ,

{ f ( e 2 π 3 ) = 0 e 2 π 2018 3 + A e 2 π 3 + B 2018 = 0 e 4 π 3 + A e 2 π 3 + B 2018 = 0 f ( e 2 π 3 ) = 0 e 2 π 2018 3 + A e 2 π 3 + B 2018 = 0 e 4 π 3 + A e 2 π 3 + B 2018 = 0 \begin{cases} f(e^{\cfrac{2\pi}{3}})=0\Rightarrow e^{\cfrac{2\pi\cdot 2018}{3}}+Ae^{\cfrac{2\pi}{3}}+B-2018=0\Rightarrow e^{\cfrac{4\pi}{3}}+Ae^{\cfrac{2\pi}{3}}+B-2018=0 \\ f(e^{-\cfrac{2\pi}{3}})=0\Rightarrow e^{\cfrac{-2\pi\cdot 2018}{3}}+Ae^{\cfrac{-2\pi}{3}}+B-2018=0\Rightarrow e^{\cfrac{-4\pi}{3}}+Ae^{\cfrac{-2\pi}{3}}+B-2018=0 \end{cases}

{ c o s 4 π 3 + i s i n 4 π 3 + A ( c o s 2 π 3 + i s i n 2 π 3 ) + B 2018 = 0 c o s 4 π 3 + i s i n 4 π 3 + A ( c o s 2 π 3 + i s i n 2 π 3 ) + B 2018 = 0 \Rightarrow \begin{cases} cos\cfrac{4\pi}{3}+isin\cfrac{4\pi}{3}+A(cos\cfrac{2\pi}{3}+isin\cfrac{2\pi}{3})+B-2018=0 \\ cos\cfrac{-4\pi}{3}+isin\cfrac{-4\pi}{3}+A(cos\cfrac{-2\pi}{3}+isin\cfrac{-2\pi}{3})+B-2018=0 \end{cases}

{ 1 2 i 3 2 + A ( 1 2 + i 3 2 ) + B 2018 = 0 ( 1 2 1 2 A + B 2018 ) + i ( 3 2 + 3 2 A ) = 0 1 2 + i 3 2 + A ( 1 2 + i 3 2 ) + B 2018 = 0 ( 1 2 1 2 A + B 2018 ) + i ( 3 2 3 2 A ) = 0 \Rightarrow \begin{cases} \cfrac{-1}{2}-i\cfrac{\sqrt{3}}{2}+A(\cfrac{-1}{2}+i\cfrac{\sqrt{3}}{2})+B-2018=0\Rightarrow (-\cfrac{1}{2}-\cfrac{1}{2}A+B-2018)+i(-\cfrac{\sqrt{3}}{2}+\cfrac{\sqrt{3}}{2}A)=0 \\ \cfrac{-1}{2}+i\cfrac{\sqrt{3}}{2}+A(\cfrac{-1}{2}+i\cfrac{-\sqrt{3}}{2})+B-2018=0\Rightarrow (-\cfrac{1}{2}-\cfrac{1}{2}A+B-2018)+i(\cfrac{\sqrt{3}}{2}-\cfrac{\sqrt{3}}{2}A)=0 \end{cases}

By comparing coefficients,

{ 1 2 1 2 A + B 2018 = 0 3 2 3 2 A = 0 \begin{cases} -\cfrac{1}{2}-\cfrac{1}{2}A+B-2018=0 \\ \cfrac{\sqrt{3}}{2}-\cfrac{\sqrt{3}}{2}A=0 \end{cases}

A = 1 , 1 2 1 2 + B 2018 = 0 B 2018 1 = 0 B = 2019 A=1, -\cfrac{1}{2}-\cfrac{1}{2}+B-2018=0\Rightarrow B-2018-1=0\Rightarrow B=2019

A + B = 2020 \therefore A+B=2020

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...